Ruptured bronchial artery aneurysm mimicking aortic dissection. - Hall, R J (1977)
A patient is presented in whom rupture of a bronchial artery aneurysm produced a clinical picture indistinguishable from an aortic dissection. This case emphasises the importance of considering alternative diagnoses when a patient presents with symptoms typical of a particular condition.